Gender and Lexical Representation in Enid Blyton’s The Famous Five: A Corpus-based Study - Vathanalaoha, Kriangkrai; Jeeradhanawin, Dhanakorn (Journal of Studies in the English Language, 2016)
Corpus stylistics is deemed promising in literary school as it fosters cautious optimism in using empirical evidence to support individualistic interpretations. Also, it is established that we are living in a digital era where texts are produced more in form of electronic text. This study aims to use corpus-based analyses to offer empirical data that reveals about language behavior of what literary critics have been studied in The Famous Five, one of the most popular series of children’s literature in the world, with respect to literary themes and gender representation. The study uses two corpus analysis tools, Wmatrix and AntConc, to generate information such as key semantic fields (thematic categorizations), collocations and concordances. Using the corpus-based information, this paper concludes that The Famous Five comprises the essence of adventures and mysteries and that the story contains conventional stereotypes of male and female protagonists. Amongst the entire group, George, or Georgina, is the most intriguing character because she has been represented as an impatient and outspoken character, characterized by the lexical choices that the author has made. Keywords: corpus stylistics; gender representation; lexical representation